Hello :
<span>If f(x)=x/2-2 and g(x)=2x^2+x-3, find (f+g)(x)
</span>(f+g)(x)= f(x) +g(x) = x/2-2 +2x²+x-3 = x/2 +2x²+x-5
(f+g)(x)= (x+4x²-2x-10) /2
(f+g)(x)= (4x²+3x-10)/2 = 2x²+3/2 x -5
The answer is
7.9306Using the formula in the attached:
Where: xi = sample value; μ = sample mean; n = sample size
1.) Calculate the mean first:
μ = 12.0 + 18.3 + 29.6 + 14.3 + 27.8 / 5
= 102 / 5
μ = 20.4
2.) Using the mean, calculate (xi - μ)² for each value:
(12.0 - 20.4)² = 70.56
(18.3 - 20.4)² = 4.41
(29.6 - 20.4)² = 84.64
(14.3 - 20.4)² = 37.21
(27.8 - 20.4)² = 54.76
3.) Sum the squared differences and divide by n - 1.
μ = 70.56 + 4.41 + 84.64 + 37.21 + 54.76
= 251.58 / 5-1
μ =
62.895 (this is now called sample variance)
4.) Get the square root of the sample variance:
√62.895 =
7.9306
Answer: 3.75 g
Step-by-step explanation:
Assume the weight of the square is x.
The hanger is in balance so the left side is equal to the right side.
Equation therefore is:
Triangle + Square + 3 * circle = 5* square + circle
3 + x + (3 * 6) = 5x + 6
3 + x + 18 = 5x + 6
5x - x = 3 + 18 - 6
4x = 15
x = 15/4
x = 3.75 g
Answer: 23
Step-by-step explanation: a P e X
Using the Polynomial Division: Divide 5
−2
+2x−4 using long polynomial division.
Answer to the Polynomial Division: ![5x^{2} -12x+37+\frac{-122x+109}{x^{2}+2x-4}](https://tex.z-dn.net/?f=5x%5E%7B2%7D%20-12x%2B37%2B%5Cfrac%7B-122x%2B109%7D%7Bx%5E%7B2%7D%2B2x-4%7D)